Compact Dual-Layer Bandpass Filter Using Novel Stepped-Impedance Resonators. Issue 1 (2nd January 2016) - Gan, D.-C.; He, S.-B.; Sun, M.-J.; Wei, X.-B.; Tang, W.; Shi, Y.
ABSTRACT: In this article, a compact third-order bandpass filter with high-frequency selectivity using novel dual-band stepped-impedance resonators is presented. In the proposed novel dual-band stepped-impedance resonator, the conventional low-impedance stub of the stepped-impedance resonator is replaced by a closed rectangular loop. The high-impedance stub is embedded in the closed loop for more compact structure. Multiple transmission zeros are introduced near the passband to improve the frequency selectivity and stopband performance. The proposed filter was designed, simulated, and fabricated to verify the validity of the proposed method. The measured results show that the center frequency is 2.83 GHz with a fractional bandwidth of 9.32%, and five transmission zeros were introduced near the passband, which are located at 1.76 GHz with 70.2-dB rejection, 2.53 GHz with 30.7-dB rejection, 3.95 GHz with 67.2-dB rejection, 8.85 GHz with 45.5-dB rejection, and 12.3 GHz with 34.5-dB rejection, respectively. The circuit only occupies 0.11λ g × 0.08λ g .